2019
DOI: 10.1002/jtr.2269
|View full text |Cite|
|
Sign up to set email alerts
|

Do people who travel more perform better at work?

Abstract: In this study, we examined how travel experiences affect job performance by improving generic skills and self-efficacy. We collected data using a questionnaire delivered to 232 Japanese employees working for a temporary employment agency. Additionally, an objective measurement (financial data) was used to assess employees' job performance level. The results revealed that travel experiences positively influenced job performance as mediated by generic skills and general self-efficacy. In addition to offering imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…This is surprising, because diary studies on recovery episodes of shorter durations, like evening hours or weekends, indicate that employees who start their workday feeling mentally and physically refreshed report higher task performance ( Binnewies et al, 2008 ). A recent study by Miyakawa et al (2019) showed that travel frequency was related to an increase in generic skills (e.g., effective communication) and in the long run with employees´ monthly salary.…”
Section: Introductionmentioning
confidence: 99%
“…This is surprising, because diary studies on recovery episodes of shorter durations, like evening hours or weekends, indicate that employees who start their workday feeling mentally and physically refreshed report higher task performance ( Binnewies et al, 2008 ). A recent study by Miyakawa et al (2019) showed that travel frequency was related to an increase in generic skills (e.g., effective communication) and in the long run with employees´ monthly salary.…”
Section: Introductionmentioning
confidence: 99%
“…En el contexto educativo, lo anterior implica, por un lado, dar un nuevo signicado a las prácticas de clases para posibilitar la transversalidad de una formación integral bajo una propuesta curricular exible. Y por otro, evidencia la inecacia de la mera impartición de conocimientos técnicos, característica de la concepción mecanicista del proceso de enseñanza-aprendizaje tradicional, y conmina invertir tiempo para adquirir nuevas habilidades que posibiliten adaptarse rápidamente a los cambios y obtener buenos resultados (Miyakawa, Kawakubo & Oguchi, 2019).…”
Section: Introductionunclassified
“…Based on recent research findings, the positive impact of travel on labour productivity has been empirically proven. Travel contributes to the formation of generic skills such as problem solving, time management, communication skills, which, in turn, contribute to human self-efficacy thus enhancing labour productivity (Miyakawa et al, 2019). Despite the fact that in that study the tourist is the subject, the basis for identifying causal relationships is a model of the influence of leisure on personal well-being, including five triggers: restoration through detachment-recovery, autonomy, mas-tery, meaning, and affiliation (Newman et al, 2014).…”
mentioning
confidence: 99%